Dynamic Microbiome Changes Reveal the Effect of 1-Methylcyclopropene Treatment on Reducing Post-harvest Fruit Decay in “Doyenne du Comice” Pear - Zhang, Yang; Gao, Congcong; Masum, Md. Mahidul Islam; Cheng, Yudou; Wei, Chuangqi; Guan, Yeqing; Guan, Junfeng (Frontiers in Microbiology, 2021)
The decay induced by pathogens is one of the major causes of fruit loss, leading to great economic loss and threatening human health. As an ethylene action inhibitor, 1-methylcyclopropene (1-MCP) can significantly reduce fruit decay, but its effect on fruit pathogens is still unclear. Herein, the variation of microbial community structure was analyzed by using the high-throughput sequencing technology and characteristics related to fruit quality were determined after 1-MCP (1.0 μL L-1) treatment in ‘Doyenne du Comiceis’ pear fruit during storage at ambient temperature. Overall, 1-MCP was highly effective in reducing disease incidence, and induced multiple changes of the fungal and bacterial microbiota. Microbial diversity of fungi or bacteria was reduced significantly at day 15 in the control fruit (non-treated with 1-MCP), which had the most serious decay occurrence. For fungi, in addition to Alternaria being the most abundant in both 1-MCP treatment (59.89%) and control (40.18%), the abundances of Botryosphaeria (16.75%), Penicillium (8.81%) and Fusarium (6.47%) increased significantly with the extension of storage time and became the main pathogens to cause fruit decay in control, while they were markedly decreased in 1-MCP treatment and thereby reduced the disease incidence. For bacteria, the abundance of Gluconobacter (50.89%) increased dramatically at day 15 in the control fruit, showing that it also played a crucial role in fruit decay. In addition, Botryosphaeria, Fusarium fungi and Massilia, Kineococcus bacteria were identified as biomarkers to distinguish 1-MCP treatment and control by using Radom forest analysis. The redundancy analysis result showed that the amount of Botryosphaeria, Penicillium and Fusarium were positively correlated with disease incidence and respiration rate of pear fruit, while being negatively correlated with fruit firmness. This investigation is the first comprehensive analysis of the microbiome response to 1-MCP treatment in postharvest pear fruit, and to reveal the relationship between fruit decay and microbial composition in pear fruit.